Porphyrin compound and perovskite solar cell containing porphyrin compound
By doping or coating porphyrin compounds in perovskite solar cells to form an iodine adsorption layer, the performance instability caused by iodine leakage in perovskite solar cells is solved, and higher stability and longer life are achieved, while simplifying the preparation process.
Patent Information
- Application Number
- CN202411522562.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The leakage of iodine elements in perovskite solar cells leads to unstable performance, and the adsorption performance of existing iodine adsorption materials is poor, and the synthesis is complex, which increases the preparation cost and engineering complexity.
Doping porphyrin compounds in the perovskite layer of perovskite solar cells or a layer of iodine adsorption layer containing porphyrin compounds is provided on the perovskite layer, which takes advantage of its efficient adsorption and stabilization of iodine elements.
It effectively solves the problem of iodine leakage in perovskite solar cells, improves the stability and life of the overall device, and reduces the preparation cost and engineering complexity.
Smart Images

Figure CN119569742A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porphyrin compound and a perovskite solar cell comprising the porphyrin compound. Background Art
[0002] Perovskite solar cells have attracted much attention due to their advantages such as simple process, low cost and high photoelectric conversion efficiency. Currently, under laboratory conditions, the efficiency of small-area perovskite solar cells has reached an astonishing 26.7%, which is close to the photoelectric conversion efficiency of silicon-based solar cells. However, the commercialization of perovskite solar cells still faces many problems, mainly including stability and environmental safety issues.
[0003] In perovskite solar cells, iodide is usually used as one of the photosensitive materials. During long-term use, iodine leakage may occur. This leakage may have a negative impact on the performance stability of the battery, and may also cause corrosion of the material and even cause environmental and health safety issues.
[0004] Currently reported iodine adsorption materials, such as patent documents CN110508248B, CN113070034B, CN109569522B, etc., have poor adsorption performance, are not stable enough in long-term use, and have more complex synthesis and processing requirements. They are not suitable for perovskite solar cells and will increase preparation costs and engineering complexity.
[0005] Therefore, it is necessary to develop efficient adsorbents for iodine in perovskite solar cells, provide new solutions for the preparation of efficient, stable and environmentally friendly perovskite solar cells, and promote the industrial development of perovskite solar cells. Summary of the invention
[0006] In order to solve one of the above-mentioned technical problems existing in the prior art, the present invention dopes a porphyrin compound into the perovskite layer of the perovskite solar cell and / or arranges an iodine adsorption layer containing the porphyrin compound on the perovskite layer to give full play to its function of efficiently adsorbing and stabilizing the iodine element, thereby effectively solving the problem of iodine leakage of the perovskite solar cell and improving the stability and life of the overall device.
[0007] In a first aspect, the present invention provides a porphyrin compound having a structure shown in Formula I or Formula II:
[0008]
[0009] In Formula I, R1 to R4 are the same or different and are each independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, each R is independently selected from H or C1-6 alkyl, and M is selected from Fe, Mn, Co, Ni, Cu, Zn, Ti or Li;
[0010] In formula II, R5 to R8 are the same or different and are independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and each R is independently selected from H or C1-6 alkyl.
[0011] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl or isohexyl.
[0012] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H or C1-4 alkyl.
[0013] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl or ethyl.
[0014] According to some embodiments of the present invention, in Formula I, R1 to R4 are the same or different, and are each independently selected from phenyl, aminophenyl and pyridyl.
[0015] According to some embodiments of the present invention, in Formula I, M is selected from Mn, Co, Ni, Cu and Zn.
[0016] According to some embodiments of the present invention, in Formula I, at least two of R1 to R4 are the same, for example, any two of R1 to R4 are the same, any three of R1 to R4 are the same, or R1 to R4 are the same. In some embodiments, any three of R1 to R4 are the same. In some embodiments, R1 to R4 are the same.
[0017] According to some embodiments of the present invention, in Formula II, R5 to R8 are the same or different and are each independently selected from phenyl, aminophenyl and pyridyl.
[0018] According to some embodiments of the present invention, in Formula II, at least two of R5 to R8 are the same, for example, any two of R5 to R8 are the same, any three of R5 to R8 are the same, or R5 to R8 are all the same. In some embodiments, any three of R5 to R8 are the same. In some embodiments, R5 to R8 are all the same.
[0019] According to some embodiments of the present invention, the porphyrin compound is selected from the group consisting of the following compounds:
[0020]
[0021] A second aspect of the present invention provides a perovskite solar cell, comprising a perovskite layer, and an optional iodine adsorption layer disposed on the perovskite layer, wherein the perovskite layer is doped with a compound represented by Formula I or Formula II, or the iodine adsorption layer comprises a compound represented by the following Formula I or Formula II, or the perovskite layer is doped with a compound represented by Formula I or Formula II, and the iodine adsorption layer comprises a compound represented by the following Formula I or Formula II:
[0022]
[0023] In Formula I, R1 to R4 are the same or different and are each independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, each R is independently selected from H or C1-6 alkyl, and M is selected from Fe, Mn, Co, Ni, Cu, Zn, Ti or Li;
[0024] In formula II, R5 to R8 are the same or different and are independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and each R is independently selected from H or C1-6 alkyl.
[0025] According to some embodiments of the invention, M is selected from Co, Ni, Cu, Zn, Ti or Li. According to some embodiments of the invention, M is selected from Co, Ni, Cu or Zn.
[0026] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl or isohexyl.
[0027] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H or C1-4 alkyl.
[0028] According to some embodiments of the present invention, in Formula I and Formula II, each R is independently selected from H, methyl or ethyl.
[0029] According to some embodiments of the present invention, in Formula I, R1 to R4 are the same or different, and are each independently selected from phenyl, aminophenyl and pyridyl.
[0030] According to some embodiments of the present invention, in Formula I, at least two of R1 to R4 are the same, for example, any two of R1 to R4 are the same, any three of R1 to R4 are the same, or R1 to R4 are the same. In some embodiments, any three of R1 to R4 are the same. In some embodiments, R1 to R4 are the same.
[0031] According to some embodiments of the present invention, in Formula II, R5 to R8 are the same or different and are each independently selected from phenyl, aminophenyl and pyridyl.
[0032] According to some embodiments of the present invention, in Formula II, at least two of R5 to R8 are the same, for example, any two of R5 to R8 are the same, any three of R5 to R8 are the same, or R5 to R8 are all the same. In some embodiments, any three of R5 to R8 are the same. In some embodiments, R5 to R8 are all the same.
[0033] According to some embodiments of the present invention, the porphyrin compound is selected from the group consisting of the following compounds:
[0034]
[0035]
[0036] According to some preferred embodiments of the present invention, the porphyrin compound has a structure shown in the following formula:
[0037]
[0038] According to some embodiments of the present invention, the perovskite solar cell further includes a transparent electrode, an electron transport layer, a TiO2 mesoporous layer, a hole transport layer and a metal electrode.
[0039] According to some embodiments of the present invention, the perovskite solar cell includes, from bottom to top, a transparent electrode, an electron transport layer, a TiO2 mesoporous layer, a perovskite layer, an iodine adsorption layer, a hole transport layer and a metal electrode.
[0040] In the present invention, the conductive material used for the transparent electrode includes but is not limited to: fluorine-doped tin oxide (FTO), tin-doped indium oxide (ITO) or aluminum-doped zinc oxide, etc. In some specific embodiments, the conductive material used for the transparent electrode includes fluorine-doped tin oxide (FTO).
[0041] In the present invention, the material of the electron transport layer includes but is not limited to: magnesium oxide, zinc oxide, titanium oxide and tin oxide. In some specific embodiments, the material of the electron transport layer includes ZnO-MgO-EA + In some specific embodiments, the material of the electron transport layer includes ZnO-MgO-EA + and Ti(Oi-Pr) 4. In some embodiments, the electron transport layer is a TiO 2 dense layer.
[0042] In the present invention, the material of the perovskite layer includes but is not limited to an organic-inorganic hybrid material ABX3, wherein A represents an organic amine cation (such as a methylamine cation, a formamidinium cation) and / or a cesium ion, and B represents Pb 2+ Sn 2+Any one of; X represents iodine, chlorine, bromine. In some embodiments, the material of the perovskite layer includes APbI3, wherein A represents an organic amine cation (such as a methylamine cation, a formamidinium cation) and / or a cesium ion.
[0043] In the present invention, the material of the hole transport layer includes but is not limited to: Spiro-MeOTAD, CuSCN, etc. In some specific embodiments, the material of the hole transport layer includes Spiro-MeOTAD.
[0044] In the present invention, the metal electrode may be gold (Au), silver (Ag), etc. In some specific embodiments, the metal electrode is a gold electrode.
[0045] A third aspect of the present invention provides a method for preparing the above-mentioned perovskite solar cell, which comprises the following steps:
[0046] (1) coating an electron transport layer and a mesoporous TiO2 layer on a transparent electrode in sequence, and then coating a perovskite precursor solution containing the porphyrin compound on the mesoporous TiO2 layer to obtain a porphyrin-containing perovskite layer; optionally, coating a solution of the porphyrin compound on the perovskite layer to obtain an iodine adsorption layer;
[0047] (2) A hole transport layer and a metal electrode are sequentially coated on the iodine adsorption layer to obtain the perovskite solar cell.
[0048] According to some embodiments of the present invention, in step (1), the perovskite precursor solution contains iodide, and the iodide preferably includes one or more of lead iodide, methylammonium iodide, iodoformamidine and alkali metal iodide.
[0049] According to some embodiments of the present invention, in step (1), the perovskite precursor solution includes a porphyrin compound, formamidine hydroiodide (FAI), methylamine hydrobromide (MABr), PbI2, CsI and RbI.
[0050] According to some embodiments of the present invention, in step (1), the solvent in the perovskite precursor solution includes DMF and / or DMSO.
[0051] According to some embodiments of the present invention, in step (1), the perovskite precursor solution contains lead iodide, and the porphyrin compound accounts for 0.1-1.0% of the molar amount of lead iodide, for example 0.1%, 0.3%, 0.5%, 0.8%, 1.0% or any value therebetween.
[0052] According to some embodiments of the present invention, in step (1), in the porphyrin compound solution, the concentration of the porphyrin compound is 1-15 mg / mL, for example, 1 mg / mL, 2 mg / mL, 5 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL or any value therebetween. In some embodiments, in step (1), in the porphyrin compound solution, the concentration of the porphyrin compound is 1-10 mg / mL.
[0053] According to some embodiments of the present invention, in step (1), the solvent in the solution of the porphyrin compound comprises a halogenated alkane, preferably dichloromethane and / or chloroform.
[0054] According to some embodiments of the present invention, in step (1), the thickness of the porphyrin-containing perovskite layer is 400-600 nm.
[0055] According to some embodiments of the present invention, in step (1), the thickness of the iodine adsorption layer is 10-30 nm.
[0056] In the present invention, the transparent electrode can be obtained by laser etching the FTO glass substrate.
[0057] In some embodiments, the above step (1) includes:
[0058] (S11) coating Ti(Oi-Pr)4 (0.15M i-PrOH solution) onto the transparent electrode, and annealing at a high temperature (e.g., 450°C-550°C) (e.g., 20-40 minutes) to obtain a dense TiO2 layer;
[0059] (S12) placing the above substrate in a pre-prepared TiCl4 solution, heating, and coating the mesoporous TiO2 slurry on the TiO2 dense layer after drying, and annealing at a high temperature (e.g., 450° C.-550° C.) (e.g., 20-40 minutes) to obtain a mesoporous TiO2 layer;
[0060] (S13) coating a perovskite precursor solution containing the porphyrin compound on the mesoporous TiO2 layer to obtain a perovskite layer containing porphyrin; and optionally
[0061] (S14) coating the solution of the porphyrin compound on the perovskite layer to obtain an iodine adsorption layer.
[0062] In some embodiments, in step (S11), the concentration of the Ti(Oi-Pr)4 solution is 0.1-0.2 M, for example, 0.15 M. In some embodiments, in step (S11), the coating speed is 2500-3000 rpm and the coating time is 20-40 s.
[0063] In some embodiments, in step (S12), the concentration of the TiCl4 solution is 0.5-1.5M, preferably 1M. In some embodiments, in step (S12), the heating temperature is 60-80°C, and the heating time is 8-15 minutes. In some embodiments, in step (S12), the mesoporous TiO2 slurry comprises an isopropanol solution of TiO2, preferably, the mass ratio of TiO2 to isopropanol is 1:(5-10). In some embodiments, in step (S12), the coating method is spin coating. The spin coating speed is 4500-5500rpm; the time is 20-40s.
[0064] In a third aspect, the present invention provides the use of the compound represented by the following formula I or formula II as an iodine adsorbent and / or in a perovskite solar cell:
[0065]
[0066] In Formula I, R1 to R4 are the same or different and are each independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, R is selected from H or C1-6 alkyl, and M is selected from Co, Ni, Cu, Zn, Ti or Li;
[0067] In formula II, R5 to R8 are the same or different and are independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and R is selected from H or C1-6 alkyl.
[0068] According to some embodiments of the present invention, in Formula I, R1 to R4 are the same or different, and are each independently selected from phenyl, aminophenyl and pyridyl.
[0069] According to some embodiments of the present invention, in Formula I, at least two of R1 to R4 are the same, for example, any two of R1 to R4 are the same, any three of R1 to R4 are the same, or R1 to R4 are the same. In some embodiments, any three of R1 to R4 are the same. In some embodiments, R1 to R4 are the same.
[0070] According to some embodiments of the present invention, in Formula II, R5 to R8 are the same or different and are each independently selected from phenyl, aminophenyl and pyridyl.
[0071] According to some embodiments of the present invention, in Formula II, at least two of R5 to R8 are the same, for example, any two of R5 to R8 are the same, any three of R5 to R8 are the same, or R5 to R8 are all the same. In some embodiments, any three of R5 to R8 are the same. In some embodiments, R5 to R8 are all the same.
[0072] According to some embodiments of the present invention, the porphyrin compound is selected from the group consisting of the following compounds:
[0073]
[0074] Compared with the prior art, the present invention has the following beneficial effects:
[0075] 1. The present invention uses a porphyrin compound with excellent iodine adsorption performance as an efficient adsorbent for iodine, thereby improving the stability of perovskite solar cells while achieving the fixation and adsorption of iodine in the device, providing a new strategy for preparing efficient, stable and environmentally friendly perovskite solar cells.
[0076] 2. In the structure of perovskite solar cells, the perovskite layer contains photosensitive materials containing iodide, which are easily affected by external factors in the natural environment, resulting in instability and dissociation of the crystal structure, and ultimately causing a decline in battery performance. The present application adopts a post-processing method in the preparation process of perovskite solar cells, that is, after the perovskite layer is crystallized, a layer of porphyrin compound material is coated thereon, thereby achieving fixed adsorption of the iodine element in the perovskite layer to improve the structural stability of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 The iodine adsorption effect of the tetrapyridinephenylporphyrin tested in Example 1 of the present application is shown.
[0078] Figure 2 The iodine adsorption effect of tetraaminophenylporphyrin tested in Example 1 of the present application is shown.
[0079] Figure 3 The iodine adsorption effect of diaminophenylporphyrin tested in Example 1 of the present application is shown.
[0080] Figure 4 The iodine adsorption effect of the monoaminophenylporphyrin tested in Example 1 of the present application is shown.
[0081] Figure 5 The iodine adsorption effect of the porphyrin cobalt complex tested in Example 1 of the present application is shown.
[0082] Figure 6 The iodine adsorption effect of the porphyrin nickel complex tested in Example 1 of the present application is shown.
[0083] Figure 7 The iodine adsorption effect of the porphyrin copper complex tested in Example 1 of the present application is shown.
[0084] Figure 8 The iodine adsorption effect of the porphyrin zinc complex tested in Example 1 of the present application is shown.
[0085] Fig. 9The iodine adsorption effect of the octaethylmonoaminophenylnickel porphyrin complex tested in Example 1 of the present application is shown.
[0086] Fig.10 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 2 of the present invention is shown.
[0087] Fig.11 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 3 of the present invention is shown.
[0088] Fig.12 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 4 of the present invention is shown.
[0089] Fig.13 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 5 of the present invention is shown.
[0090] Fig.14 The photoelectric conversion efficiency of the perovskite solar cell prepared in Example 6 of the present invention is shown.
[0091] Fig.15 The light stability test results of the perovskite solar cells prepared in Examples 2 and 5 of the present invention are shown.
[0092] Fig.16 The iodine adsorption performance test results of the perovskite film before and after CuP treatment are shown.
[0093] Fig.17 The UV-Vis spectrum test results of the perovskite film before and after CuP treatment in the iodine adsorption experiment are shown. DETAILED DESCRIPTION
[0094] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.
[0095] The reagents used in the following experiments of the present invention, unless otherwise specified, are all conventional commercial products or reagents prepared by conventional methods, and the methods used in the experiments, unless otherwise specified, are all conventional experimental methods. The instruments used in the experiments, unless otherwise specified, can all be obtained through commercial channels.
[0096] The tetrapyridylphenylporphyrin, tetraaminophenylporphyrin and diaminophenylporphyrin used in the present invention are obtained through commercial routes.
[0097] The synthetic chemicals such as meso-tetraphenylporphyrin, N,N-dimethylformamide, dimethyl sulfoxide, metal acetate, 3,4-diethylpyrrole and benzaldehyde were purchased from J&K Technology Co., Ltd., the solvents such as ether and acetic acid were purchased from Sichuan Cologne Science Co., Ltd., trifluoroacetic acid was purchased from TCI Chemical Industry Development Co., Ltd., and iodine was purchased from Sigma-Aldrich. The materials used in the examples were directly used or synthesized based on the above materials.
[0098] FTO conductive glass, laser etcher (JW-20W-KS, Wuhan Junwei Technology), spin coater (JW-A5, Wuhan Junwei Technology), solar simulator (Newport), vacuum coater (Micro-Nano Vacuum VZZ-300), iodine (Sigma-Aldrich), zinc acetate (J&K Technology Co., Ltd.), magnesium acetate (J&K Technology Co., Ltd.), etc. are all commercially available reagents and were used directly without additional treatment.
[0099] Synthesis Example 1 Synthesis of Monoaminophenylporphyrin (Por)
[0100] The synthetic route is as follows:
[0101]
[0102] Add 10 mL of TFA to tetraphenylporphyrin, then slowly add sodium nitrite in an equivalent of 1 / 1.8, stir at room temperature for 3 min, add water to quench the reaction, and extract with dichloromethane. Wash the organic layer with a saturated aqueous solution of NaHCO3, and then evaporate the solvent in a vacuum. After evaporation of dichloromethane, the product is dispersed in concentrated hydrochloric acid (10 mL), and 6 equivalents of stannous chloride are added. Heat the reaction solution to 60 ° C for 6 hours, cool to room temperature, collect the solid residue, dissolve it with dichloromethane, and wash it to pH = 8. Concentrate the organic layer, dry it, and purify the product by silica gel column chromatography, elute with dichloromethane, and evaporate the solvent in a vacuum to obtain compound Por.
[0103] Synthesis Example 2 Synthesis of Monoaminophenylporphyrin Metal Complex
[0104] The synthetic route is as follows:
[0105]
[0106] The synthesis steps are as follows:
[0107] Dissolve monoaminophenylporphyrin in chloroform (100 mL), add excess Co(OAc)2, Cu(OAc)2, Zn(OAc)2 in methanol (10 mL) respectively. Reflux the mixture at 65°C for 4 hours. Monitor the reaction under UV light. After the reaction is completed, extract with water three times, remove the solvent under reduced pressure, and obtain monoaminophenylporphyrin cobalt complex CoP, monoaminophenylporphyrin copper complex CuP, and monoaminophenylporphyrin zinc complex ZnP respectively.
[0108] Monoaminophenylporphyrin was dissolved in DMF, and an excess of Ni(OAc)2·4H2O was added, and the mixed solution was refluxed at 110°C for 4 hours. The reaction was monitored by UV light. After the reaction was completed, the solution was extracted with water three times, and the solvent was removed under reduced pressure to obtain monoaminophenylporphyrin nickel complex NiP.
[0109] Synthesis Example 3 Synthesis of Octaethylmonoaminophenylnickelporphyrin (NiOP)
[0110]
[0111] 3,4-Diethylpyrrole (360 μL) and benzaldehyde (268 μL) were added to 125 mL of acetic acid. The mixture was refluxed for 2 hours. After the reaction was completed, the solvent was removed. The residue was dissolved in dichloromethane and washed with saturated sodium bicarbonate until the washing solution was alkaline. The organic phase was concentrated and purified by silica gel column chromatography using dichloromethane / methanol (1:2%, v / v) as eluent. Recrystallization from the eluent gave a green solid to synthesize 2,3,7,8,12,13,17,18-octaethyl-5,10,15,20-tetraphenylporphyrin (H2OETPP).
[0112] 1.4 equivalents of NaNO2 were slowly added to a concentrated solution of H2OETPP in TFA for 3 minutes to produce mainly mononitroporphyrin, which was quenched with water after completion of the reaction. The solvent was removed, and then, the nitroporphyrin was reduced to the corresponding aminoporphyrin using an excess of stannous chloride dihydrate in an HCl solution. The resulting aminoporphyrin was separated by silica gel chromatography using dichloromethane / methanol as an eluent. The eluent was concentrated to obtain a green solid to obtain octaethyl monoaminophenylporphyrin (Por1).
[0113] Referring to the method of Synthesis Example 2, "monoaminophenylporphyrin" was replaced with "octaethylmonoaminophenylporphyrin (Por1)" to obtain octaethylmonoaminophenylnickelporphyrin (NiOP).
[0114] Example 1: Test of iodine adsorption effect of porphyrin
[0115] Tetrapyridylphenylporphyrin, tetraaminophenylporphyrin, diaminophenylporphyrin, monoaminophenylporphyrin and the five porphyrin metal complexes CoP, CuP, ZnP, NiP and NiOP obtained in the above synthesis examples 1-3 were used as adsorbents to test the iodine adsorption capacity. The static adsorption test was used to test the adsorption capacity of porphyrin for I2 vapor in order to evaluate the adsorption capacity of different porphyrins for I2.
[0116] Two powder samples of porphyrin and iodine were placed in a sealed bottle and then heated at 75°C. The mass change of porphyrin was measured at intervals. The results were as follows: Figures 1 to 9 As shown in Figure 2, the iodine adsorption capacity of porphyrin increases with time. Figures 1 to 9 It can also be observed that several porphyrin compounds show significant adsorption performance for iodine, among which tetrapyridyl porphyrin has the best adsorption effect on iodine, with an adsorption amount of up to 6.48g / g. In addition, tetraaminophenyl porphyrin and monoaminophenyl copper porphyrin also have good iodine adsorption effects, with adsorption amounts of 6.25g / g and 5.87g / g, respectively. Considering solubility and other issues, monoaminophenyl copper porphyrin CuP was selected as a passivator and introduced into perovskite solar cells.
[0117] Example 2: Preparation of perovskite solar cells
[0118] The FTO glass was etched with a laser etcher to obtain an electrode pattern, and then ultrasonically washed with acetone, water, and ethanol for 10 minutes in sequence. The glass substrate was blown dry and treated with UV ozone for 15 minutes. Ti(Oi-Pr)4 (0.15M i-PrOH solution) was then spin-coated on the FTO glass substrate (2800rpm, 25s), followed by annealing at 500℃ for 30 minutes to complete the preparation of the dense layer. After cooling to room temperature, the substrate was immersed in a 1M TiCl4 solution at 70℃ and heated for 12 minutes. After drying, mesoporous TiO2 (slurry: isopropanol 1:8, mass ratio) was spin-coated at 5000rpm, 25s, and then annealed at 500℃ for 30 minutes. 167.03mg FAI, 22.28mg MABr and 599.31mg PbI2 were dissolved in a mixed solution of DMF and DMSO (743μL:186μL), and then 47.8μL (1.5M) of CsI DMSO solution and 46.9μL (1.5M) of RbI DMSO solution were added to prepare the perovskite precursor solution. The perovskite precursor solution was spin-coated in a nitrogen glove box (800-4000rpm, 10-30s), and a dense perovskite film with a thickness of 500nm was obtained after annealing. The hole transport layer Spiro-OMeTAD was spin-coated at 4000rpm. Finally, 80nm of gold was evaporated using a vacuum coating instrument, and the cell efficiency was tested under a solar simulator.
[0119] Example 3: Preparation of perovskite solar cells doped with monoaminophenyl copper porphyrin (CuP)
[0120] The preparation of the perovskite precursor solution in this example is the same as that in Example 2.
[0121] The FTO glass was etched with a laser etcher to obtain an electrode pattern, and then ultrasonically washed with acetone, water, and ethanol for 10 minutes in sequence. The glass substrate was blown dry and treated with UV ozone for 15 minutes. Ti(Oi-Pr)4 (0.15M i-PrOH solution) was then spin-coated on the FTO glass substrate (2800rpm, 25s), followed by annealing at 500℃ for 30 minutes to complete the preparation of the dense layer. After cooling to room temperature, the substrate was immersed in a 1M TiCl4 solution at 70℃ and heated for 12 minutes. After drying, mesoporous TiO2 (slurry: isopropanol 1:8, mass ratio) was spin-coated at 5000rpm, 25s, and then annealed at 500℃ for 30 minutes. 0.5% CuP was added to the above perovskite precursor solution (molar ratio relative to PbI2 0.5%), and spin-coated in a nitrogen glove box (800-4000rpm, 10-30s), and a dense perovskite film with a thickness of 500nm was obtained after annealing. The hole transport layer Spiro-OMeTAD was spin-coated at 4000rpm. Finally, 80nm of gold was evaporated using a vacuum coating instrument, and the cell efficiency was tested under a solar simulator.
[0122] Example 4
[0123] The difference from Example 3 is that after the dense perovskite film is prepared, a layer of CuP chloroform solution (the concentration of monoaminophenylporphyrin copper is 1 mg / mL) is spin-coated (4000 rpm, 25 s) on the perovskite film to obtain an iodine adsorption layer; and then a hole transport layer is spin-coated.
[0124] Example 5
[0125] The difference from Example 3 is that after the dense perovskite film is prepared, a layer of CuP chloroform solution (monoaminophenylporphyrin copper concentration is 5 mg / mL) is spin-coated (4000 rpm, 25 s) on the perovskite film to obtain an iodine adsorption layer with a thickness of about 20 nm; and then a hole transport layer is spin-coated.
[0126] Example 6
[0127] The difference from Example 3 is that after the dense perovskite film is prepared, a layer of CuP chloroform solution (monoaminophenylporphyrin copper concentration is 10 mg / mL) is spin-coated (4000 rpm, 25 s) on the perovskite film to obtain an iodine adsorption layer; and then a hole transport layer is spin-coated.
[0128] Experiment 1: Photovoltaic conversion efficiency test of perovskite solar cells
[0129] The photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 2-6 was tested by performing a current-voltage curve (IV) test on a device equipped with a Keithley 2400 source meter and an LSH-7320ABA LED light simulator (Newport). Before the test, the light intensity was calibrated to 100 mW·cm using a standard silicon cell. -2 , which is the AM 1.5G sunlight condition. The results are as follows Figure 10-14 As shown, the perovskite solar cell prepared in Example 3 exhibits the best photoelectric conversion efficiency.
[0130] The control perovskite solar cell in Example 2 was tested under a solar simulator and the cell efficiency was only 21.18% ( Fig.10 ).
[0131] Example 3: The perovskite solar cell prepared by doping 0.5% CuP in perovskite has a cell efficiency of 22.18% ( Fig.11 ).
[0132] Example 4: The perovskite solar cell prepared by spin coating 1 mg / mL CuP on the perovskite layer was tested under a solar simulator and the cell efficiency was 21.76% ( Fig.12 ).
[0133] Example 5: The perovskite solar cell prepared by spin coating 5 mg / mL CuP on the perovskite layer was tested under a solar simulator and the cell efficiency was 22.06% ( Fig.13 ).
[0134] Example 6 The perovskite solar cell prepared by spin coating 10 mg / mL CuP on the perovskite layer was tested under a solar simulator and the cell efficiency was 20.07% ( Fig.14 ).
[0135] Experiment 2: Light stability test of perovskite solar cells
[0136] In the light condition test, the perovskite solar cell prepared by post-treating the perovskite layer with iodine adsorption layer using a 5 mg / mL monoaminophenyl copper porphyrin solution in Example 5 also showed excellent stability. Fig.15 As shown, after 20 hours of light stability test, the battery structure of the device not treated with the porphyrin metal complex has been completely destroyed and decomposed, while the device of Example 5 treated with the porphyrin metal complex CuP still maintains a good morphology.
[0137] Experiment 3: Perovskite solar cell device stability and iodine adsorption performance test
[0138] A conventional iodine-starch color reaction was used to evaluate the adsorption capacity of CuP for released iodine in the perovskite film. The perovskite film before and after treatment with CuP was placed in a glass tube with 1 mL of starch aqueous solution at the bottom. The glass tube was continuously irradiated under AM1.5G light. After 1 hour of illumination, the starch aqueous solution of the control device changed from colorless to purple, which was clearly visible to the naked eye. In contrast, under the same lighting conditions, the starch aqueous solution of the CuP-based device remained colorless ( Fig.16 ). The results show that the introduced CuP can effectively inhibit the release of iodine from the device, indicating that the CuP-treated device has excellent iodine adsorption performance.
[0139] Since I2 and the movable I - Ions react easily to produce triiodide ions (I3 - ), so the starch aqueous solution in the above glass tube was replaced with water to further quantify the iodine vapor emission of the device. Fig.17 As shown in Figure 2, after 20 hours of irradiation, the release of iodine was evaluated using UV-visible spectroscopy. The results showed that the control group had a significant I3 - The absorption peak of the sample treated with CuP is almost negligible. It can be observed that the iodine content released by the perovskite solar cell treated with CuP is greatly reduced, which proves the effectiveness of this treatment strategy.
[0140] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A porphyrin compound having a structure shown in Formula I or Formula II: In Formula I, R1 to R4 are the same or different and are each independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, each R is independently selected from H or C1-6 alkyl, and M is selected from Fe, Mn, Co, Ni, Cu, Zn, Ti or Li; In formula II, R5 to R8 are the same or different and are independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and each R is independently selected from H or C1-6 alkyl.
2. The porphyrin compound according to claim 1, characterized in that In formula I, R1 to R4 are the same or different and are each independently selected from phenyl, aminophenyl and pyridyl; each R is independently selected from H, methyl, ethyl; and / or, In formula II, R5 to R8 are the same or different and are independently selected from phenyl, aminophenyl and pyridyl; each R is independently selected from H, methyl and ethyl.
3. The porphyrin compound according to claim 1 or 2, characterized in that In Formula I, at least two of R1 to R4 are the same, preferably at least three are the same; in Formula II, at least two of R5 to R8 are the same, preferably at least three are the same; Preferably, the porphyrin compound is selected from the group consisting of the following compounds:
4. A perovskite solar cell, comprising a perovskite layer, and optionally an iodine adsorption layer disposed on the perovskite layer, wherein the perovskite layer is doped with the porphyrin compound according to any one of claims 1 to 3, and / or the iodine adsorption layer contains the porphyrin compound according to any one of claims 1 to 3; Preferably, the porphyrin compound has a structure shown in the following formula:
5. The perovskite solar cell according to claim 4, characterized in that: The perovskite solar cell also includes a transparent electrode, an electron transport layer, a hole transport layer and a metal electrode; Preferably, the perovskite solar cell comprises, from bottom to top, a transparent electrode, an electron transport layer, a TiO2 mesoporous layer, a perovskite layer, an iodine adsorption layer, a hole transport layer and a metal electrode.
6. A method for preparing a perovskite solar cell as claimed in claim 4 or 5, comprising the following steps: (1) coating an electron transport layer and a mesoporous TiO2 layer on a transparent electrode in sequence, and then coating a perovskite precursor solution containing the porphyrin compound on the mesoporous TiO2 layer to obtain a perovskite layer containing porphyrin; Optionally, coating a solution of the porphyrin compound on the perovskite layer to obtain an iodine adsorption layer; (2) A hole transport layer and a metal electrode are sequentially coated on the perovskite layer or the iodine adsorption layer to obtain the perovskite solar cell.
7. The method according to claim 6, characterized in that In step (1), the perovskite precursor solution contains iodide, and the iodide preferably includes one or more of lead iodide, methylammonium iodide, iodomethane, and alkali metal iodide; and / or, In step (1), the perovskite precursor solution comprises a porphyrin compound, formamidine hydroiodide, methylamine hydrobromide, PbI2, CsI and RbI; and / or, In step (1), the perovskite precursor solution contains lead iodide, and the porphyrin compound accounts for 0.1-1.0% of the molar amount of lead iodide, preferably 0.3-0.8%; and / or, In step (1), in the solution of the porphyrin compound, the concentration of the porphyrin compound is 1-15 mg / mL; and / or, In step (1), the solvent in the solution of the porphyrin compound comprises a halogenated alkane, preferably dichloromethane and / or chloroform; and / or, In step (1), the thickness of the porphyrin-containing perovskite layer is 400-600 nm; and / or, In step (1), the thickness of the iodine adsorption layer is 10-30 nm.
8. Use of the porphyrin compound represented by the following formula I or formula II as an iodine adsorbent and / or in a perovskite solar cell: In Formula I, R1 to R4 are the same or different and are each independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, each R is independently selected from H or C1-6 alkyl, and M is selected from Fe, Mn, Co, Ni, Cu, Zn, Ti or Li; In formula II, R5 to R8 are the same or different and are independently selected from phenyl, hydroxyphenyl, carboxyphenyl, aminophenyl, methoxyphenyl and pyridyl, and each R is independently selected from H or C1-6 alkyl.
9. The use according to claim 8, characterized in that: In Formula I, R1 to R4 are the same or different and are each independently selected from phenyl, aminophenyl and pyridyl, and each R is independently selected from H, methyl and ethyl; In formula II, R5 to R8 are the same or different and are each independently selected from phenyl, aminophenyl and pyridyl, and each R is independently selected from H, methyl and ethyl.
10. The use according to claim 8 or 9, characterized in that: In Formula I, at least two of R1 to R4 are the same, preferably at least three are the same; in Formula II, at least two of R5 to R8 are the same, preferably at least three are the same; Preferably, the porphyrin compound is selected from the group consisting of the following compounds:
Citation Information
Patent Citations
An iodine adsorbent material, its preparation method and application
CN109569522B
An iodine adsorbent material and its preparation method
CN110508248B
An iodine adsorbent material and its preparation method
CN113070034B
Method for efficiently and stably preparing large-area perovskite solar cell based on porphyrin doping
CN109860394A
Perovskite solar cell
CN111755607A